2018
DOI: 10.1002/jbm.b.34262
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting of hydrogel‐based biomimetic microenvironments

Abstract: Three‐dimensional (3D) bioprinting is a promising technology to produce cell‐laden constructs via patterning living cells, biological factors and biomaterials in a precisely controlled manner. However, it is still a challenge to fabricate human tissues/organs with biological functions for clinical application via 3D bioprinting. Several key issues should be carefully addressed to overcome this challenge, specifically the construction of biomimetic microenvironments. 3D printing has been broadly demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 108 publications
0
40
0
Order By: Relevance
“…Notably the rigidity, the surface properties, the chemical/biochemical composition, the permeability to cells and the degradability are critical factors controlling cell fate and tissue homeostasis. For this reason, hydrogels are among the best candidates as inks for printing 3D scaffolds for cell culture [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Notably the rigidity, the surface properties, the chemical/biochemical composition, the permeability to cells and the degradability are critical factors controlling cell fate and tissue homeostasis. For this reason, hydrogels are among the best candidates as inks for printing 3D scaffolds for cell culture [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been successful in guiding the fate of microparticle‐adhered cell unitary blocks, or through incorporation in cell‐laden bioinks. The latter is particularly valuable, since the direct incorporation of growth factors in bioinks results in rapid diffusion, often reducing bioactive molecules overall concentration comparing to that achieved with sustained presentation via microparticle‐mediated controlled delivery . Researchers have explored these microparticles features for instance by incorporating gelatin microparticles loaded with either VEGF or BMP‐2 into bioinks for achieving accelerated osteodifferentiation and regional angiogenesis on bioprinted 3D living constructs with well‐defined architecture .…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%
“…[6][7][8][9] Taking inspiration from the ECM, which plays an important role not only as a mechanical support but also as a key functional regulator for tissue maturation, considerable efforts have been made to develop hydrogels that recreate the composition or properties of native articular cartilage to guide tissue-specific formation. [10][11][12][13] Currently, tissue-derived dECM (t-dECM) is considered a promising biomaterial since it is a direct way to provide the complex composition of native tissue, which is difficult to reproduce using common biomaterials. Results from studies about cartilage-derived ECM as hydrogel revealed chondro-inductivity and potential for supporting new matrix synthesis, without the need for further functionalization.…”
Section: Introductionmentioning
confidence: 99%